The second face of a known player: Arabidopsis silencing suppressor AtXRN4 acts organ-specifically - Vogel, Florian; Hofius, Daniel; Paulus, Kathrin Elisabeth; Jungkunz, Isabel; Sonnewald, Uwe (New Phytologist, 2011)
Subsequent analysis of MP17:GFP transcript stability in xrn2 and xrn3 mutants indicated an essential role of AtXRN2 for silencing suppression in roots/cotyledons while AtXRN3 appears to act similar to AtXRN4 in source leaves, only. Overall, these findings point towards an organ-specific regulation of gene silencing in Arabidopsis.
Keywords: movement protein; plasmodesmata; silencing; silencing suppression; virus resistance; XRN